Depression and anxiety among chronic anal fissure patients. (September 2022) - El Muhtaseb, M.S.; Salameh, Mohammad; Al-Mikhi, Bana; Abed Alfattah, Amer; Hamsho, Firas; Braizat, Zain; Alsheikh, Farah; Khouri, Diala; Haimour, Shahed; Addasi, Rami; Alsaadi, Tabarak; Al-husban, Naser; et al.
Abstract: Introduction: /Aims: Anal fissures are common disorders characterized by extreme pain, difficult defecation, and altered quality of life. The etiology of such condition is not entirely elucidated as it is implicated that stress could be an etiologic factor of anal fissures. Therefore, this study aims to evaluate the mental health of patients with chronic anal fissures in an effort to demonstrate the link between psychiatric disorders and anal fissures. Method: ology: All patients clinically diagnosed with chronic anal fissures attending the surgery clinics were recruited prospectively into this study over a 4-month period (from October 2020 to February 2021). During the clinic visit, patients were examined for chronic anal fissures as well as evaluated for depression, anxiety, and sleep disturbances using the PHQ-9, GAD-7, and PSQI scores pre and post the 3-months treatment period. Results: This study included a total of 51 patients clinically diagnosed with chronic anal fissures. The sample has an average age of41.8 ± 14.5 years and an average time of 7.1 ± 22.1 months since the start of their symptoms. The most frequent symptoms across the sample included pain while defecating (92.2%), severe constipation (52.9%), and bloody stool (45.1%).During follow up after 3 months treatment, our analysis showed that the means of PHQ9, GAD7, and PSQI scores were significantly lower than at diagnosis (pre-treatment) (All, p < 0.01). Moreover, pain intensity, distress, and interference means were all significantly lower than their values prior to treatment (All, p < 0.01). Conclusion: We concluded that the quality of life for patients with chronic anal fissures is impacted by pain, psychiatric disorders and sleep disturbances. Therapy should be attainable, cheap, effective and focused on enhancing sleep alterations, in addition to targeting psychiatric symptoms. Highlights: Chronic anal fissures report significant degrees of pain, psychiatric symptoms, and sleep disturbances. Therapy of these patients should be effective, inexpensive, and well-tolerated. Depression, Anxiety, pain intensity, distress were all significantly lower than their values prior to treatment.